External fixator (Compressor-distractor) for fracture correction: pseudoarthrosis, lengthening or bone transposition. - Espinoza M., A.; Valencia O., R. (Revista Mexicana de Ingenieria Biomedica, 1989)
We present an apparatus that contains six dozen fewer pieces than those usually used for the correction of fractures, pseudoarthrosis or in bone lengthening and transportation treatments. The fixative was applied in 18 patients of very varied pathologies, obtaining satisfactory results. The advantages of this new device are discussed with respect to conventional techniques.